Applying the conceptual framework of “event religion” to two Hungarian festivals - Heidl, Sára Eszter (Svetovi (Ljubljana), 2024)
The event religion framework has been developed to enable the study of event experience using the tools of sociology, ethnography and religious studies, independently of the religious affiliation of the event participants or the events themselves. It examines event experience along four dimensions: spatiotemporality, symbols, community, and inward experience. This paper examines the event religion dimensions at a Catholic and a rock-metal music event in Hungary in order to draw attention to similarities and differences in participant experiences at a religious and a nonreligious festival.
Keywords: dogodki; duhovnost; empirical fieldwork; empirično terensko delo; event; Fekete Zaj; festivali; festivals; Lélek; Madžarska; prireditve; religija; religion; religionesknost; religionesque; spirituality